Pelestarian Makanan Tradisional Kejos Sebagai Sumber Karbohidrat Di Desa Tarikolot Kecamatan Jatinunggal Kabupaten Sumedang Provinsi Jawa Barat - Rahmalianti, Risa; Nur Alia, Mirna; Riyadi, Dony (Universitas Pendidikan Indonesia, 2016)
This research is focused on discuss about traditional food which is based on cassava, it is called kejos and it is rarely found in Tarikolot subdistrict Jatinunggal district Sumedang Province Jawa Barat now. This traditional food have a good taste and has a property glut Such as rice. Kejos which is based on cassava has a good potensial, because it can grow in every weather and every year. And it is also can be found everywhere.There is a lot of nutritions in cassava such as carbohydrate. The level ofcarbohydrate in cassava if we compared with rice is the third. First is rice and thesecond is corn. This traditional food is also has a story to citizen in Tarikolot thattime. It will be disappointed if this traditional food disappear.Therefore, the writer make some innovation to make this traditional foodbecome popular.